An Event Study Analysis of Green Bond Issuance: Signaling Corporate Commitment and Market Perception in an Emerging Economy (The Case of PT XYZ, Indonesia) - Saskia Arumaisa Rizna; Desi Adhariani (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines the short-term stock market reaction to the green bond issuance announcement by PT XYZ, a publicly listed Indonesian bank, using an event study methodology. The analysis focuses on the announcement date of 21 June 2022 as the event day and applies an eleven-trading-day event window (t−5 to t+5) to capture both pre-announcement and post-announcement market responses. Abnormal Return (AR) and Cumulative Abnormal Return (CAR) are calculated using the Mean Adjusted Return Model, which is appropriate for descriptive single-firm event studies over short horizons. The results reveal a significant positive abnormal return of 4.17% on the event day, indicating that investors initially perceived the green bond issuance as value-relevant information and a credible sustainability signal. However, abnormal returns exhibited volatility in the post-event period, and cumulative abnormal returns progressively adjusted toward their pre-event level, suggesting efficient incorporation of information and short-term market efficiency. Interpreted through the lens of Signaling Theory, the findings indicate that green bond issuance functions as a credible corporate signal that generates immediate investor response, although its valuation impact is transitory. This study contributes to the green finance literature by providing event study evidence from an emerging market context and highlights the role of credibility in shaping short-term investor reactions to sustainability-linked corporate actions.